Breaking barriers: a commentary on research gaps in cancer and depression among individuals with intellectual disabilities - Lara Carneiro; Rita Vaičekauskaitė; Oliwia Kowalczyk; Katarzyna Ćwirynkało (International Journal for Equity in Health)
Abstract The European Commission’s Strategy for the Rights of Persons with Disabilities 2021–2030 aims to ensure equal opportunities and rights for all individuals, including those with intellectual disabilities. People with intellectual disabilities are often underrepresented in cancer prevention and screening policies, leading to disparities in health outcomes and early mortality. The intersection of intellectual disability, cancer, and depression represents an underexplored area in healthcare research. Individuals with intellectual disability diagnosed with both cancer and depression face compounded challenges impacting their quality of life, proper access to medical care, and treatment outcomes. To address these gaps in the systems globally, a focused effort is indispensable to understand their unique needs and better tailor care strategies for this target group. Therefore, this commentary outlines the challenges in researching individuals with intellectual disabilities who have a dual diagnosis of cancer and depression. Challenges include providing informed consent, ethical researcher–participant relationships, and maintaining confidentiality and autonomy. Strategies for improvement include creating accessible procedures, raising awareness, and involving individuals with intellectual disabilities in research ethics committees.